ตัวประกอบภาวะผู้นำของพยาบาลหัวหน้าหอผู้ป่วยตามความต้องการ ของพยาบาลประจำการโรงพยาบาล สังกัดกระทรวงกลาโหม - วาสินี วิเศษฤทธิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 1996)
The purposes of this research were to investigate the leadership factors of head nurses as desired by staff nurses and the variables described those major factors. The sample consisted of 960 staff nurses, who have had at least 1 year experience in clinic in 34 hospitals under the jurisdiction of the Ministry of Defense. They were randomly selected through systematic sampling technique. The reliability of the instrument, calculated by the Cronbach s Alpha Coefficient, was 0.97. The data were analysed by using Principal Component Factor Analysis, Orthogonal rotated axis by Varimax method. The major findings were as follows. Nine significant leadership factors of head nurses were identified : 1) change strategies, values driven, supervision and professional attributes which described by 18 variables and accounted for 31.4%, was a major factor of leadership of head nurses as desired by staff nurses, 2) positive contingency reinforcement which described by 14 variables and accounted for 5.7%, 3) intellectual stimulation which described by 13 variables and accounted for 3.2%, 4) charisma and ethics which described by 18 variables and accounted for 2.4%, 5) inspiration which described by 11 variables and accounted for 2.3%, 6) enabling subordinates which described by 7 variables and accounted for 1.9%, 7) negative contingency reinforcement which described by 7 variables and accounted for 1.9%, 8) facillitating of work autonomy and participation which described by 5 variables and accounted for 1.6%, 9) individual consideration which described by 3 variables and accounted for 1.4%. The total variance of these factors was 49.39 (51.5%)